2023
DOI: 10.1111/bld.12527
|View full text |Cite
|
Sign up to set email alerts
|

‘It should be more outspoken and not hushed away, not like put in a dark box’: An interpretative phenomenological analysis of experiences of menopause voiced by women with learning disabilities

Abstract: BackgroundThere is little research into experiences of menopause voiced by women with learning disabilities, who can be neglected in academic research. There is a particular lack of knowledge around the psychological and social experiences of menopause in this population, and how changes are managed. This study sought to explore these experiences.MethodsExperiences of five women with lived experience of menopause, being seen by community National Health Services specialising in learning disabilities, were capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The scoping review of the literature found that attention to the topic of menstruation and learning disability has fallen over the last two decades with only two of the included UK-based papers being published within the last five years. The lack of recent empirical studies on menstruation and learning disability may be related in part to significant barriers in recruitment practices, as documented by Langer-Shapland et al (2023); detailed further in a follow-up paper for In Response (Millear et al, 2023). This implies that the most recent generation of women with learning disabilities is not sufficiently included in the evidence base, which is a notable concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review of the literature found that attention to the topic of menstruation and learning disability has fallen over the last two decades with only two of the included UK-based papers being published within the last five years. The lack of recent empirical studies on menstruation and learning disability may be related in part to significant barriers in recruitment practices, as documented by Langer-Shapland et al (2023); detailed further in a follow-up paper for In Response (Millear et al, 2023). This implies that the most recent generation of women with learning disabilities is not sufficiently included in the evidence base, which is a notable concern.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies also tend to focus on specific stages of menstruation such as menopause rather than taking a life course approach to the topic. The experiences of different phases are potentially related as a lack of knowledge about the menstrual cycle could impact later confusion and experience of menopause (Langer-Shapland et al, 2023;Moore et al, 2023). McCarthy (2002a) questions whether the distinct phases of the lifecycle are meaningful/experienced in the same way by women with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%